Climate change impacts on the Mediterranean Coastal Zones - Frédéric Brochier; Emiliano Ramieri (Fondazione Eni Enrico Mattei (FEEM), 2001)
Climate change is widely recognised as a serious threat to the world's environment. The Mediterranean basin is considered as a unique scaled down model to assess the severity of potential climate change impacts on coastal zones. The paper examines the regional differences in the vulnerability of Mediterranean coastal zones from existing studies and projections for the future. The objective is to work within the uncertainty constraints associated with local projections and quantitative impact assessments in order to provide a complete picture of potential impacts and also to identify possible response measures. Major impacts such as increased erosion, intensification of floods, saltwater intrusion and loss of habitat will be of particular concern on deltas, islands, wetlands and historic coastal cities. However, although Mediterranean coasts will experience greater stress produced by non climatic factors - population increase, urbanisation, tourism - the paper highlights the necessity to combine efforts to minimise damage and to integrate adaptation strategies in a broad "Integrated Coastal Zone Management" programme.
Keywords: O13; Q20; Q25; 330; Coastal zones; climate change; impacts; Mediterranean basin; sea level rise; vulnerability; Klimawandel; Küstenregion; Mittelmeerraum; Küstenschutz